Foreign Language Education and Translation: Between Economic Returns and Cognitive Culture - Othman, Asmaa (Ta'amul: Journal of Islamic Economics, 2024)
re increasingly significant in the context of human existence, particularly in the modern global economy. This study explores the intersection of language education and translation from an economic perspective, considering language as a vehicle for the exchange of intangible assets and currency as a medium for tangible assets. Just as translation involves transferring meaning across linguistic systems, currency exchange facilitates the transfer of goods and values across economic systems. Thus, foreign language acquisition parallels foreign currency trading, and translation mirrors the conversion of commodities. The main objective of this research is to investigate the complex relationships between language, translation, and economics. It raises key theoretical questions: What is the economic value of language and translation? Can language be considered a form of currency? How does language learning foster creative thinking? Is foreign language education an economic necessity in the modern era? Does translation influence economic systems? Using a comparative and analytical method, the study draws parallels between linguistic and economic systems, examining the mutual dynamics of market expansion and language spread. It also investigates how the rise of unified European languages coincided with the emergence of standardized currencies and common markets. Findings suggest that language has evolved into a marketable commodity, subject to regional and global economic forces. This research contributes to the interdisciplinary discourse linking language education, translation studies, and economic theory, offering new insights into how language functions as both a communicative tool and an economic asset in the knowledge-driven global market.